WORKING MOTHER'S KNOWLEDGE ON HOW TO STORAGE ASI IN POSYANDU MATAHARI ,THE WORKING AREA OF THE PUSKESMAS BOTANIA - Wenas Wenas; Muhammad Dezarino (Universitas Batam, 2020)
Background : Exclusive breastfeeding is the best food for babies, but in its implementation there are many obstacles, one of which is the mother working so that she has to leave the baby at home. Working mothers can still do exclusive breastfeeding by expressing milk in the workplace, and providing four clean and closed ones for expressing. The target for achieving exclusive breastfeeding set by the Ministry of Health is 80%, while in Indonesia in 2015 the target was 71.62%. The purpose of this study was to determine the knowledge of working mothers on how to store breast milk. Method : The research method used was descriptive, carried out at the Matahari Posyandu, the working area of the Botania Community Health Center, the study was conducted for 6 months, the population in this study were all working mothers who had babies 0-12, the sample was 43 people with the sampling technique using total sampling, instrument. research using a questionnaire. Result : The results showed that most of the respondents had good knowledge, namely 35 people (81.4%), while 8 people (18.6%) had poor knowledge. Conclusion : The conclusion that can be taken is that most working mothers who have babies have knowledge. good about how to store breast milk. It is recommended that the mother of the baby is always looking for information about breast milk so that she can continue to give her breast milk